Short Communication: The detection of Plasmodium in mosquitoes from Sumba and Sorong districts, Indonesia - MUNIRAH MUNIRAH; ISRA WAHID; FIRDAUS HAMID; Sitti Wahyuni (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Munirah M, Wahid I, Hamid F, Wahyuni S. 2021. Short Communication: The detection of Plasmodium in mosquitoes from Sumba and Sorong districts, Indonesia. Biodiversitas 22: 2680-2684. Malaria is heading for elimination in 2030, but the disease remains prevalent in Indonesia. Therefore, this study aimed to determine a vector other than Anopheles that is potentially responsible for malaria transmission in the country's endemic areas. The mosquitoes were trapped by Kelambu trap, collected using a mouth aspirator, and stored in a tube containing silica gel. They were also examined microscopically following O'Connor identification keys, and Nested PCR was used to detect Plasmodium DNA. The number of mosquitoes collected from two areas was 1.336. In Sumba (Gaura village) district, 493 mosquitoes were captured, and the dominant genus was Anopheles (58.6%), followed by Culex (31%), Armigeres (9.9%), Aedes (0.2%), and Lutzia (0.2%). Among 843 mosquitoes collected from Sorong (Aimas), Culex was 98.9%, followed by Aedes (0.8%) and Anopheles (0.2%). The result of nested PCR found two An. sundaicus from Sumba carried Plasmodium which belongs to P. falciparum and P. vivax species (0.14%). Although we did not detect the presence of Plasmodium in mosquitoes other than the genus Anopheles, in this study, we found Anopheles species that have never previously been reported from the area, namely An. bailey and An. barbirostris from Papua and An. nivipes in West Sumba.